RETRACTED: Unmanned aerial vehicle for monitoring transport infrastructure - Kim K.K.; Koroleva E.B.; Vataev A.S.; Tkachuk A.A.; Monastyrsky D.Ya. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001